2016
DOI: 10.1590/0370-44672015690122
|View full text |Cite
|
Sign up to set email alerts
|

Texture evolution in the Fe-30.5Mn-8.0Al-1.2C and Fe-30.5Mn-2.1Al-1.2C steels upon cold rolling

Abstract: Crystallographic textures of the austenitic low-density Fe-30.5Mn-8.0Al-1.2C (8Al) and Fe-30.5Mn-2.1Al-1.2C (2Al) (wt.%) steels were examined during cold rolling by means of electron backscatter diffraction (EBSD) and electron channeling contrast imaging (ECCI). Random oriented grains orient towards Goss-and brass-components along the α-fiber as the strain increased, with activation of slip, mechanical twinning, and shear banding, for both steels. S-and copper-orientations were also observed in the 8Al steel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…However, the influence of twinning on texture development needs to be paid more attentions. For the Fe-Mn-Al-C TWIP steels, Souza et al suggested that the texture transition from copper to brass texture was observed at higher reduction influenced by deformation twins with strong similarity to that found in Fe-Mn-C TWIP steels [21]. However, this issue should be investigated for Fe-Mn-Si-Al TWIP steels.…”
Section: Introductionmentioning
confidence: 96%
“…However, the influence of twinning on texture development needs to be paid more attentions. For the Fe-Mn-Al-C TWIP steels, Souza et al suggested that the texture transition from copper to brass texture was observed at higher reduction influenced by deformation twins with strong similarity to that found in Fe-Mn-C TWIP steels [21]. However, this issue should be investigated for Fe-Mn-Si-Al TWIP steels.…”
Section: Introductionmentioning
confidence: 96%